Dietary Flaxseed Independently Lowers Circulating Cholesterol and Lowers It beyond the Effects of Cholesterol-Lowering Medications Alone in Patients with Peripheral Artery Disease. Issue 4 (18th February 2015) - Edel, Andrea L; Rodriguez-Leyva, Delfin; Maddaford, Thane G; Caligiuri, Stephanie PB; Austria, J Alejandro; Weighell, Wendy; Guzman, Randolph; Aliani, Michel; Pierce, Grant N
Abstract: Background: Dietary flaxseed lowers cholesterol in healthy subjects with mild biomarkers of cardiovascular disease (CVD). Objective: The aim was to investigate the effects of dietary flaxseed on plasma cholesterol in a patient population with clinically significant CVD and in those administered cholesterol-lowering medications (CLMs), primarily statins. Methods: This double-blind, randomized, placebo-controlled trial examined the effects of a diet supplemented for 12 mo with foods that contained either 30 g of milled flaxseed [milled flaxseed treatment (FX) group; n = 58] or 30 g of whole wheat [placebo (PL) group; n = 52] in a patient population with peripheral artery disease (PAD). Plasma lipids were measured at 0, 1, 6, and 12 mo. Results: Dietary flaxseed in PAD patients resulted in a 15% reduction in circulating LDL cholesterol as early as 1 mo into the trial ( P = 0.05). The concentration in the FX group (2.1 ± 0.10 mmol/L) tended to be less than in the PL group (2.5 ± 0.2 mmol/L) at 6 mo ( P = 0.12), but not at 12 mo ( P = 0.33). Total cholesterol also tended to be lower in the FX group than in the PL group at 1 mo (11%, P = 0.05) and 6 mo (11%, P = 0.07), but not at 12 mo ( P = 0.24). In a subgroup of patients taking flaxseed and CLM ( n = 36), LDL-cholesterol concentrations were lowered by 8.5% ± 3.0% compared with baseline after 12 mo. This differed from the PL + CLM subgroup ( n = 26), which increased by 3.0% ± 4.4% ( P = 0.030) to a final concentration of 2.2 ± 0.1 mmol/L. Conclusions: Milled flaxseed lowers total and LDL cholesterol in patients with PAD and has additional LDL-cholesterol–lowering capabilities when used in conjunction with CLMs. This trial was registered at clinicaltrials.gov as NCT00781950.